NEW POSSIBILITIES OF ANTIBACTERIAL TREATMENT IN ACUTE AND CHRONIC RESPIRATORY DISORDERS IN CHILDREN - O. I. Simonova; A. V. Lazareva; O. V. Motuzova; O. A. Ponamorenko; L. K. Katosova; V. P. Chistyakova; N. I. Burkina ("Paediatrician" Publishers LLC, 2013)
The authors show the data on current microbiological pattern in children with acute and chronic respiratory disorders and dynamics of microflora susceptibility to the most frequently used antibiotics over recent years. The principles of antibiotic choice and control for their efficiency, peculiarities of their usage in children and the most common side effects are given. New aspects of the usage of combined antibacterial agents - ecoantibiotics - are discussed. Including of the Lactulose Anhydro into their composition allows to achieve high microbiological efficacy and does not cause antibiotic-induced diarrhea, which has a great importance in pediatric practice.